1986
DOI: 10.1179/mst.1986.2.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic deformation behaviour of martensitic–ferritic dual-phase steels

Abstract: The deformation behaviour of the two phases of three plain carbon dual-phase steels after various treatments has been studied using a scanning electron microscope equipped with a tensile straining stage. The distribution of strains between the ferrite and martensite phases, as well as among the different grains of each phase, was observed to be inhomogeneous. The martensite/ferrite strain ratio, which defines the degree of uniformity of straining between the phases, depends on the microstructural parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(6 citation statements)
references
References 10 publications
(3 reference statements)
2
4
0
Order By: Relevance
“…This result can be regarded as mechanical property of microstructure and conforms to the observation of Ref. [44][45][46]. The trend of dislocation mean free path of Martensite in Fig.…”
Section: Local Deformationsupporting
confidence: 84%
“…This result can be regarded as mechanical property of microstructure and conforms to the observation of Ref. [44][45][46]. The trend of dislocation mean free path of Martensite in Fig.…”
Section: Local Deformationsupporting
confidence: 84%
“…The strain ratio ε f εm decreases with increasing V m , which indicates that there is lower strain incompatibility between the phases with increasing amount of martensite in DP steels. Similar behaviour was observed experimentally by Shen et al [18] and Su and Garland [19]. The strain ratio ε f εm showed an initially increase during the early stage of deformation, followed by a subsequent decrease after reaching global strain values of around 0.03.…”
Section: Ferrite and Martensite Stress-strain Curves In Group Asupporting
confidence: 88%
“…Shen et al [13] determined the strain distribution in the ferrite and martensite phases by measuring the average relative elongations of each phase along the tensile direction in various DP steels. They reported that the macroscopic strain at which martensite deformation commenced depended on the microstructural configuration of the steel.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-scale deformation of materials has been mainly studied through the observation of microstructural evolution using different techniques including insitu mechanical testing combined with strain measurements at a microscopic scale [9,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%